Interpreting currency crises : a review of theory, evidence, and issues - Omar F. Saqib (Deutsches Institut für Wirtschaftsforschung (DIW), 2002)
The main objective of this paper is to understand the causes and symptoms of currency crises by reviewing its seminal literature, establishing its determinants, and outlining some of the relevant issues. The paper highlights the need to comprehend the process, which may lead to the inconsistency of the policies and render the situation favourable for a speculative attack. This involves, broadening the determinants of exchange rate crises beyond pure economic fundamentals through incorporating non-economic factors, such as political incentives on macroeconomic policy making. In effect, the review accentuates upon the need to develop a model that bridges the gap between the conventional and non-conventional determinants of a currency crisis.
Keywords: 330; Währungskrise; Wechselkurstheorie; Devisenspekulation; Theorie; Welt